1983
DOI: 10.1177/073428298300100308
|View full text |Cite
|
Sign up to set email alerts
|

The Freedom-From-Distractibility Factor: an Examination of Its Adaptive Behavior Correlates

Abstract: The main purpose of this study was to assess the validity of the name Freedom from Distractibility, commonly assigned to the third factor usually found on the Wechsler intelligence scales. The WAIS scores of 111 mentally retarded individuals were submitted to a factor analysis, and the resulting factors were correlated with these subjects' scores on the Adaptive Behavior Scale (ABS). It was hypothesized that if this factor was really a measure of attention, then, compared to the other factors, it should show (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Feinberg & McIlvried (1991) found that attention tasks (such as a vigilance task and a cancellation task) were moderately correlated with the Freedom From Distractibility factor in people with chronic schizophrenia. On the other hand, other research suggests that the Freedom From Distractibility factor was not related to behavioral indices of hyperactivity, a behavior presumably related to some extent to attention control, in a sample of adults with mental retardation (Rofskowski, 1983). The evidence for an association between the Freedom From Distractibility factor and executive functioning is also conflicting.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…Feinberg & McIlvried (1991) found that attention tasks (such as a vigilance task and a cancellation task) were moderately correlated with the Freedom From Distractibility factor in people with chronic schizophrenia. On the other hand, other research suggests that the Freedom From Distractibility factor was not related to behavioral indices of hyperactivity, a behavior presumably related to some extent to attention control, in a sample of adults with mental retardation (Rofskowski, 1983). The evidence for an association between the Freedom From Distractibility factor and executive functioning is also conflicting.…”
mentioning
confidence: 90%
“…Although numerous studies have delineated the factor structure of the WAIS-R using the standardization sample and various clinical groups (for a review, see Kaufman, 1990, andSattler, 1992), the construct validity of the factors has been less rigorously studied.Studies of the WAIS-R have typically identified a Verbal Comprehension factor consisting of the Vocabulary, Information, Comprehension, and Similarities subtests, and a Perceptual Organization factor, consisting most frequently of Block Design, Object Assembly, Picture Completion, and in some analyses, Picture Arrangement. The third factor in three-factor solutions, Freedom From Distractibility, usually consists of Arithmetic and Digit Span (Parker, 1983), and less consistently, Digit Symbol (Kaufman, 1990;Roszkowski, 1983).Consensus on the most stable factor structure for the WAIS-R has largely wavered between the two-and three-factor solutions. Leckliter, Matarazzo, and Silverstein (1986) concluded that the derivation of two-factor versus three-factor solution was…”
mentioning
confidence: 99%
See 3 more Smart Citations